2021
DOI: 10.1016/j.ctcp.2021.101460
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, acceptability, and potential effectiveness of an online expressive writing intervention for COVID-19 resilience

Abstract: Background & purpose The COVID-19 pandemic has negatively impacted mental health in the general population. In this trial, our objective was to assess whether a 6-week expressive writing intervention improves resilience in a sample from the general population in the midst of the COVID-19 pandemic. Materials & methods This 6-week trial was conducted online. Eligible participants (n=63) were a sample of adults who self-identified as having been significantly affected by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 32 publications
2
14
1
Order By: Relevance
“…Since the outbreak of the pandemic, several studies have examined the experience of clients and therapists in the virtual and distanced space. For example, psychodrama ( Biancalani et al, 2021 ), drama therapy ( Atsmon et al, 2022 , Wood et al, 2020 ), music therapy ( Lee et al, 2021 ), art therapy ( Biro-Hannah, 2021 , Zubala et al, 2021 ), dance movement therapy ( Lotan Mesika et al, 2021 ) and expressive writing therapy studies ( Bechard et al, 2021 ) all indicate that despite the challenges, tele-CAT is perceived as a good-enough alternative under some circumstances, such as social and geographic distancing, and may even have some benefits ( Feniger-Schaal et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the outbreak of the pandemic, several studies have examined the experience of clients and therapists in the virtual and distanced space. For example, psychodrama ( Biancalani et al, 2021 ), drama therapy ( Atsmon et al, 2022 , Wood et al, 2020 ), music therapy ( Lee et al, 2021 ), art therapy ( Biro-Hannah, 2021 , Zubala et al, 2021 ), dance movement therapy ( Lotan Mesika et al, 2021 ) and expressive writing therapy studies ( Bechard et al, 2021 ) all indicate that despite the challenges, tele-CAT is perceived as a good-enough alternative under some circumstances, such as social and geographic distancing, and may even have some benefits ( Feniger-Schaal et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Due to the rapid development of positive psychology, the research focusing on stress, trauma, and pain seemed to have been redirected to the “positive effects”, such as “posttraumatic growth,” “quality of life,” and “resilience.” Because of the pandemic, “COVID-19” has been included in studies in the past two years. Bechard et al (2021) found that the online expressive writing intervention in the general population proves effective in improving resilience during the COVID-19 pandemic. Davis et al (2020) proposed that expressive writing can promote athletes’ mental health due to disruptions to training sessions caused by the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 97%
“…Because of the pandemic, "COVID-19" has been included in studies in the past two years. Bechard et al (2021) found that the online expressive writing intervention in the general population proves effective in improving resilience during the COVID-19 pandemic. Davis et al (2020) proposed that expressive writing can promote athletes' mental health due to disruptions to training sessions caused by the COVID-19 pandemic.…”
Section: Thematic Evolution: Burst Terms Detectionmentioning
confidence: 97%
“…Over 90% of participants completed pre-study questionnaires and post-participation interviews demonstrating feasibility of the implementation of questionnaires with participation, with 77% completing post-study questionnaires. These completion rates are higher than many other similarly structured interventions, with 71% completion rate for a therapeutic songwriting intervention for those with dementia and their care givers and 73% completion rate for participation in online expressive writing intervention for COVID-19 resilience [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%